CURRENT ISSUES OF TEMIR OOZ KOMUZ’S RESTITUTION IN KYRGYZ CULTURE (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
Intangible cultural heritage objects protected by UNESCO attract close attention of representatives of oral-professional music, and current problems of their preservation are on the agenda of state cultural policy of several countries, including Kyrgyzstan. The subject of this article is the most important issues of both preserving and developing the traditional form of education on the ancient Kyrgyz musical instrument temir ooz komuz, which have been implemented by the Republican Center «Ustatshakirt» since 2003 (created on the initiative of the Aga Khan in the field of musical creativity). The topic is the problem of the traditional oral-professional forms of Kyrgyz jaw harp existence. The purpose is to describe the process of restoring oral forms of traditions of temir komuz teaching/performing, which is currently acquiring features of restitution, as, in fact, it compensates for the results of many years of the tradition’s destruction of the socio-cultural base, prevents the possible loss of cultural heritage and counteracts the extinction of an entire layer of oral-professional musical art. The results of the study showed that the Ustatshakirt center carries out successful projects to support the oral-professional musical and theatrical art tradition, as well as the manufacture of traditional Kyrgyz musical instruments. Among neighboring Central Asian countries, the long-term targeted program of resuming oral teaching of the temir ooz komuz playing, implemented by Kyrgyz theorists and practitioners, is of particular interest in light of the international achievements of outstanding Jaw harpists, including Kutmanaly Sultanbekov, recognized as one of the nine best virtuosos in the world at the Third International Competition in Yakutia in 2022. The article is intended for the attention of professional Jaw harp performers, ustat (teachers), master makers of temir ooz komuzes, as well as amateurs of Kyrgyz traditional musical art. The conclusions state that thanks to the active work of individual enthusiasts, the process of restitution of oral forms of temir komuz traditions’ existence achieves its goals, and also contributes to the promotion of Kyrgyz musical art as a whole in the international cultural space. At the same time, the most important issues of protecting national identity require support for these initiatives at the state level with the necessary and sufficient funding.
Keywords: temir ooz komuz, restitution of oral tradition, Ustatshakirt, Kutmanaaly Sultanbekov, Kyrgyz traditional musical culture.